EVALUATION OF THE REMOVAL OF PRIMER COATING IN AN AUTOMOTIVE PAINTING PROCESS, ECONOMICAL EFFECTS AND ENVIRONMENTAL IMPACT - Dalmolin, Carla; Gonçalves, Felipe Freire; Pachekoski, Wagner Mauricio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
Automotive industry worldwide faces strong pressures towards the reduction of environmental impacts caused by the productive process. At the same time, the highly competitive car market causes an increasingly constant search for cost reduction and productivity rising in this industrial segment. Facing this need for reduction on the environmental impact associated with the increase of productivity in the automotive painting processes, this study proposes the investigation of the possibility to remove the paint layer known as primer, evaluating the effects on coating properties through laboratory analysis and tests inside the production line. The laboratory tests involved the comparison between the proposed paint structure and original paint structure properties, while tests in the production line involved the evaluation of panels and prototypes. Almost all results showed that the paint system proposed works properly. The adoption of proposed paint structure would allow environmental performance gains and productivity increasing by reducing chemicals usage and atmospheric emissions.